2022
DOI: 10.1002/smll.202201075
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Multiscale Assembly via Photothermally Driven Convective Flow for Sensitive In‐Solution Plasmonic Detections

Abstract: The assembly of metal nanoparticles and targets to be detected in a small light probe volume is essential for achieving sensitive in‐solution surface‐enhanced Raman spectroscopy (SERS). Such assemblies generally require either chemical linkers or templates to overcome the random diffusion of the colloids unless the aqueous sample is dried. Here, a facile method is reported to produce 3D multiscale assemblies of various colloids ranging from molecules and nanoparticles to microparticles for sensitive in‐solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In this view, plasmonic photothermal effects of the Raman laser on LSPR metallic nanoparticles have been suggested (Figure 3d). 99 The absorbed light energy on the metallic nanoparticles' LSPR excitation is converted into thermal energy for local heating. The temperature gradient generates convective flow that collects MNPs toward the Raman laser spot site and assembles them together with the SERS nanoparticles.…”
Section: ■ Recent Advancements In Identifying Npsmentioning
confidence: 99%
“…In this view, plasmonic photothermal effects of the Raman laser on LSPR metallic nanoparticles have been suggested (Figure 3d). 99 The absorbed light energy on the metallic nanoparticles' LSPR excitation is converted into thermal energy for local heating. The temperature gradient generates convective flow that collects MNPs toward the Raman laser spot site and assembles them together with the SERS nanoparticles.…”
Section: ■ Recent Advancements In Identifying Npsmentioning
confidence: 99%
“…[6,7] Convection most of the time leads to the energy exchange and the mass transfer, and is widely used in many different systems, [8][9][10] including motion systems [11,12] and heat transfer systems. [13,14] Convection can also carry specific nanoparticles or DOI: 10.1002/advs.202307020 targeting molecules for directional transportation, which further broadens the application of convection in bio/chemical sensing systems [15,16] and separation systems. [17] Generally, the formation of the convection is the result of the nonequilibrium state inside the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, selectively concentrating targets on the detection zone is an effective strategy. Several methods have been explored, such as electrophoresis, thermo-diffusion, convection, and immiscible oil–water interfaces. , However, these approaches require additional devices and cannot be widely used. Electrokinetic preconcentration technology has been used for rapid separation and preconcentration of samples on the electrode surface. ,, Yang et al found that molecules could be loaded on the SERS substrate under electrostatic force guidance .…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, selectively concentrating targets on the detection zone is an effective strategy. Several methods have been explored, such as electrophoresis, 23 thermo-diffusion, 24 convection, 25 and immiscible oil−water interfaces. 26,27 However, these approaches require additional devices and cannot be widely used.…”
Section: Introductionmentioning
confidence: 99%